Trait anxiety and somatization levels in children with irritable bowel syndrome - M.O. Semen; O.L. Lychkovska (Zdorovʹe Rebenka, 2023)
Background. According to the biopsychosocial model of medicine, irritable bowel syndrome (IBS) is a heterogeneous disorder that occurs as a result of the complex interaction of biological, psychoemotional and psychosocial factors. Their combination is individual for each patient. The study aims to evaluate the psychoemotional features (anxiety and somatization) in children with IBS depending on the predominant bowel habit and the trigger factor in the development of the disorder. Materials and methods. We enrolled 55 children aged 6–12 years with a verified diagnosis of IBS, following Rome IV Criteria. The control group included 45 children of the same age and gender. The levels of anxiety and somatization were assessed by the Children’s Manifest Anxiety Scale and the Somatoform Symptom Screening, respectively. Results. Children with IBS had significantly higher level of anxiety (р < 0.0001) and somatization (р < 0.0001) in comparison to the control group. We have not found any significant differences in these parameters according to the predominant bowel habit. However, the analysis based on the nature of the trigger factor in the onset of the disorder revealed remarkably higher levels of anxiety (р = 0.0006) and somatization (р = 0.05) in children with stress-associated IBS. Moreover, a direct correlation between the studied parameters (r = 0.69, p < 0.0001) proves their close connection and a tendency to augment each other. Conclusions. Our study confirms a heterogeneity of IBS in children. As psychoemotional factors play a crucial role in the occurrence of IBS, it is necessary to consider them in the development of personalized care planning.